Enhanced Piezoelectric Properties of Poly(L‐lactide) Nanocomposite Microfiber Scaffolds Due to Polydopamine‐Coating of Barium Titanate Nanoparticles - Richard Schönlein; Xabier Larrañaga; Asier Panfilo; Yu Li; Aitor Larrañaga; Guoming Liu; Alejandro J. Müller; Robert Aguirresarobe; Jone M. Ugartemendia (Advanced Materials Interfaces)
Abstract Recent biomedical applications demand piezoelectric polylactide (PLA)‐based polymers, possessing biodegradable and biocompatible properties for tissue regeneration, implantable force sensors, and energy harvesting devices. However, piezoelectric poly(L‐lactide) (PLLA) possesses weak piezoelectric properties in comparison to non‐biodegradable poly(vinylidene fluoride) (PVDF), limiting its application. This contribution presents, for the first time, a nanocomposite strategy to enhance the piezoelectric properties of PLLA, while maintaining cytocompatibility. Biocompatible and piezoelectric barium titanate (BTO) nanoparticles (NPs) are coated by polydopamine (PDA) (cBTO NPs) to improve the quality of the matrix‐filler interface and enhanced the force transmission toward the BTO NPs. Electrospun PLLA/cBTO nanocomposite microfiber scaffolds with 5 wt% of PDA‐coated BTO NPs (cBTO) exhibited an increase in piezoelectric properties of 120% in comparison to pristine PLLA microfiber scaffolds, implying a voltage output increase from 1.4 ± 0.1 to 3.2 ± 0.2 V. Furthermore, the PDA‐coating of BTO (cBTO) NPs itself has an intensifying impact on the piezoelectric properties of PLLA/cBTO nanocomposite compared to non‐coated BTO NPs, increasing the voltage output by 41%. This demonstrates the great potential of PDA‐coating of piezoelectric NPs to enhance the piezoelectric response of PLLA.